(untitled) (Archives of Mechanics - Test, 1997)
The Editorial Committee of Archives of Mechanics invited the Scientific Committee of the XXXI Polish Solid Mechanics Conference — SolMec’96 organized in Mierki, September 9-14, 1996, by the Institute of Fundamental Technological Research and Committee of Mechanics of the Polish Academy of Sciences, to encourage all authors of oral and poster presentations at the SolMec’96 Conference to publish their contributions in special issues of the Archives of Mechanics and Engineering Transactions.